The Influence Of Strategic Human Capital On Organisational Performance Of Manufacturing Organisations In Malaysia - Lee, Jocelyne Jia Lin (2018)
Research on strategic human capital among Malaysian manufacturing companies is very important for the growth of the economy. This is because in manufacturing sector, the absorption and learning ability of technology is very limited as it is hindered by semi-skilled foreign workforce. As such, strategic human capital is a very useful element to ensure that the crucial and relevant technology is absorbed and utilized. Specifically, this study attempts to examine the impact of learning orientation, human resource configuration and social capital towards strategic human capital in enhancing the organisational performance. Aside from understanding the factors that trigger strategic human capital, knowledge strategy as the moderator is examined as the element that strengthens the relationship between strategic human capital and organisational performance. Data was collected from 164 large manufacturers via survey questionnaire developed from related literature and pre-tested by HR managers and academic experts. The data was analysed using partial least square-structural equation modelling via Smart PLS. Findings indicated that learning orientation, human resource configuration and social capital plays a role in strategic human capital. Knowledge strategy moderates the relationship between organisational performance and strategic human capital and it is found that more attention is paid to the financial aspect of organisational performance. This study makes both theoretical and practical contribution by identifying the elements that create strategic human capital and what construct strengthens its relationship with organisational performance. Limitations of the study were explained and suggestions for future study were also presented.